Creativity as neoliberal self-governance - Barszczewski, Jakub (Creativity Studies, 2021)
The purpose of this article is to analyze the problem of non-professional creativity in contemporary self-help literature. Creativity, an element of work organization in the post-Fordist era, has been the subject of many critical analyses. I focus on creativity as it appears in everyday life, with the support of an examination of self-help handbooks that refer to far-east traditions, at the same time being critical of the Western lifestyle. Self-help literature is viewed here as a tool aiding the neoliberal governmentality of society. I am most of all interested in how contemporary discourse on non-professional creativity promotes technologies of autonomy aimed at the production of responsible and self-sufficient individuals. I argue that creativity is today a key mechanism of governance. It is not limited to the professional sphere but is playing an increasing role in our private lives. It is used to produce more elusive and flexible forms of self-governance than more openly repressive forms of power (based on top-down order and control).